The No. 1 Ladies' Detective Agency [compact disc, unabridged] - McCall Smith, Alexander, 1948- (McCall Smith, Alexander, 1948- No. 1 Ladies Detective Agency series., 2003)
In contemporary Botswana, sleuth Precious Ramotswe decides to go against tradition and start her own business--a detective agency. Soon she is in the thick of several perplexing cases.